Evaluation of Peronema canescens Leaves Extract: Fourier Transform Infrared Analysis, Total Phenolic and Flavonoid Content, Antioxidant Capacity, and Radical Scavenger Activity - Maigoda, Tonny; Judiono, Judiono; Purkon, Dicki Bakhtiar; Haerussana, Ayu Nala El Muna; Mulyo, Gurid Pramintarto Eko (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Peronema canescens (Sungkai) leaves have been popular in Indonesia which contain various bioactive compounds with empirical therapeutic efficacy in dealing with COVID-19 and various other diseases. Total phenolic and flavonoid content and antioxidant activity using the DPPH method from P. canescens leaf extract have not been studied much. AIM: This research has several objectives. The first is to compare the results of qualitative phytochemical analysis of the ethanol extract of the leaves of P. canescens (EEPL). The second is to measure the total phenol and flavonoid content. The third is to test the FTIR and antioxidant activity of the ethanol extract of P. canescens leaves in vitro using the DPPH method. METHODS: Fresh plant material and simplicia, ethanol extract extracted by maceration method using 96% ethanol as solvent from P. canescens. The Dragendorff’s and Mayer test carried out the qualitative phytochemical analysis, FeCl3 test, Salkowski method, Liebermann–Burchard method, foam test, and NaOH reagent. The total phenolic and flavonoid levels were tested using the Folin–Ciocalteu method. In vitro antioxidant activity was carried out using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. RESULTS: The results of qualitative phytochemical screening showed that alkaloids, flavonoids, saponins, tannins, and steroids were detected in the extract of P. canescens. The spectra from the FTIR test results showed various absorbance peak values indicating the bonding of specific functional groups, namely: 418.12, 599.94, 666.67, 1036.39, 1159.52, 1224.16, 1348.95, 1454.19, 1600.87, 1732.00, 2923.13, and 3353.01 cm-1. In the test results, total phenolic content was as much as 5.64% (mgEAG/g) and total flavonoid content of 142,247 mgEQ/g in a sample of 1 mg extract, which was equivalent to 1 mg quercetin. EEPL has antioxidant activity with the DPPH IC50 method of 116.7865 ppm. CONCLUSION: The data obtained at this time can contribute to the exploitation of P. canescens leaves in the future as one of the nutraceutical products, supplements, and herbal medicines by specific industries related to improving the health status of the world community. The higher the bioactive substance in preparation, the more significant the effect of the pharmacological efficacy response. P. canescens ethanol extract has good total phenolic content, total flavonoid content, and antioxidant action.